Comment conjuguer verticalité et horizontalité dans l’organisation de la revendication au sein de l’espace occitan ? - Christian Lagarde (Lengas)
This article examines and compares the vertical and horizontal structuring of the two major linguistic and cultural organizations, the Félibrige (1854) and the Institut d'Études Occitanes (1945), as well as the relationship between their leaders and their constituencies. It also questions whether the second organization, conceived as the antithesis of the first, was in fact so.